Blockchain for Trusted Future - Kotha, Murali Mohan (International Journal of Computer Sciences and Engineering, 2019)
The third industrial revolution brought in personal computers and the Internet. Like many sectors, the financial sector was also influenced by such digitalization and the internet, which resulted in the emergence of “FinTech”. The blockchain is one of the many transformative and disruptive innovations of FinTech. The blockchain, though is relatively a new technology, has the potentiality, that it can be used in various other applications. Like the internet, which influenced the world, the blockchain is also expected to transform various operating models of finance. This in turn may result in evolution of new disruptive technological innovations. In recent years, many financial/ trade institutions across the globe, have been observing very closely, the developments in blockchain technology. The way the blockchain provides the complete confidence – with consensus, disintermediation, time-stamped and immutable recording of the linked transactions’ history, in a distributed network – is attracted by several businesses. The blockchain can be adapted in IPR, finance, internet of things, and in any transaction for that matter. The blockchain can address the multi-party systems’ inefficiencies, resulting in benefits to all. Further, the smart contract feature is useful in complex business workflows. This paper discusses structure of blockchain, its types, features, and explores some of its applications in different fields.